ENTREPRENEURIAL INTENTION IN GEN Z: THE ROLE OF FINANCIAL STRESS - Obioma Wisdom , Nwaokokorom (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
Generation Z represents younger individuals born in the midst of growing technological innovations. They are considered digital natives and are known to be entrepreneurially inclined. However, there is growing concerned about these groups' declining entrepreneurial intention. This study aimed to investigate financial stress (FS) as a previously unexplored variable that could determine the variance in EI in Gen Z. Two hundred and eleven undergraduates were randomly drawn from different institutions of higher learning in River State, Nigeria. Data for the study was gathered using the Financial Stress Scale- College Version (FSS-CV) and the Entrepreneurial Intention Questionnaire (EIQ). The result showed a significant regression equation F (1,209), = 231.83, P<.05), indicating that FS significantly predicted EI among the cohort with an R2 of 231, demonstrating that the FS contributed 23.1% of the variation in the student's EI. Thus, the study's outcome confirms the study's hypothesis that FS would significantly predict EI among Gen Z. The practical implication and recommendations are discussed.